Management of Unilateral Hyperlactation in a Mother Exclusively Breastfeeding 7-Month-Old Infant: A Case Report - Zumrotin Hasnawati; Hafiidhaturrahmah Hafiidhaturrahmah (Medical and Health Journal, 2026)
Background: Hyperlactation is a condition characterized by excessive breast milk production beyond the infant’s nutritional needs, which may lead to feeding difficulties and maternal discomfort. Unilateral hyperlactation is a rare condition and may result from idiopathic mechanisms, iatrogenic factors, or a combination of both. This case report describes the mechanism and successful management of unilateral hyperlactation occurring after contralateral breast abscess surgery. Case Report: A 24-year-old lactating mother presented with excessive milk production, breast pain, and recurrent ductal obstruction in the right breast. One month prior, she had undergone surgical drainage of a left breast abscess. Her 7-month-old infant experienced breastfeeding difficulties, green frothy stools, and excessive weight gain. The condition was diagnosed as a unilateral hyperlactation of idiopathic–iatrogenic hybrid, whereby reduced stimulation of the surgically treated left breast triggered compensatory overproduction in the right breast. A comprehensive management using Academy of Breastfeeding Medicine (ABM) protocol was implemented, including laid-back breastfeeding positioning, block feeding for 14 days, and oral pseudoephedrine 60 mg twice daily. Significant clinical improvement was observed, with reduced milk production to levels appropriate for the infant’s needs, resolution of maternal symptoms, and successful continuation of breastfeeding. Conclusion: Unilateral hyperlactation following breast surgery can be effectively managed using an ABM Protocol–based approach combining block feeding and pharmacological therapy, enabling successful continuation of breastfeeding.